ANALISIS NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL SULUH RINDU KARYA HABIBURRAHMAN EL SHIRAZY - Sapitri, Dwi Arma; Djumingin, Sulastriningsih; Baharman, Baharman (Panrita: Jurnal Bahasa dan Sastra Daerah serta Pembelajarannya, 2024)
This research aims to describe the main character and the value of character education in the novel Suluh Rindu by Habiburrahman El Shirazy. This type of research is qualitative. The instrument used in this research is human instrument or the researcher himself. The data collection technique in this research uses note-taking and documentation methods. Data analysis techniques in this research are data reduction, data categorisation and conclusion drawing. The results of this study indicate that in the novel Suluh Rindu by Habiburrahman El Shirazy there are two main characters, namely Ridho and Syifa. Ridho's character is obedient to worship, loving, disciplined, responsible, and generous. Syifa's character is hardworking, generous, disciplined, devout, and forgiving. Furthermore, in the novel Suluh Rindu by Habiburrahman El Shirazy, there are five aspects of character education, namely religion, nationalism, independence, mutual cooperation, and integrity.